Pengaruh Motivasi Kerja Terhadap Kinerja Dan Profesionalitas Guru: Studi Literatur - Abdul Khobir; Nailal Mubarokah; Nur Rahmaliya Aula Haanie; Diva Khasanadia (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
This study aims to examine and synthesize various research findings related to the influence of work motivation on teacher performance and professionalism. Using a descriptive-qualitative literature review approach, the authors analyzed 15 scholarly articles published between 2015 and 2023. The findings indicate that both intrinsic and extrinsic motivation significantly affect teacher performance and professionalism across different educational levels. Motivated teachers tend to be more innovative, disciplined, responsible, and exemplary in the school environment. Motivation also encourages continuous professional development. Although external factors such as incentives, school policies, and work climate contribute, work motivation is proven to be the most dominant internal factor influencing teacher performance and professionalism. This study also highlights the need for systemic support to sustain teacher motivation and suggests future research opportunities to explore differences between civil servant and non-civil servant teachers, the role of motivation in technology adoption, and post-pandemic challenges. These findings are expected to serve as a reference for formulating education quality improvement policies based on enhancing teacher work motivation. Keywords: Work motivation, teacher performance, professionalism, literature review.